English Blends in Indonesian Context: Their Formation Processes and Meanings - Rio Rini Diah Moehkardi (Humaniora, 2019)
This research aims at observing the blending process, the patterns of blending, and the possible new meanings of the English-influenced blends found in the Indonesian context. The influence of English and Indonesian not only in terms of the source words involved, but also of the morphological processes of the blends and also to see whether there are some semantic changes, anticipating the cultural influence of the blend creators. Data are collected from advertisement of schools events, brand name of food and beverage products, also names of cafes and restaurants found mostly in Yogyakarta. The data are analyzed using Mattiello’s formula (2013) in categorizing the process of blending: morphotactical, morphonological, and morphosemantic. The results show that morphotactically the data can be classified into total and partial blends of which there are more blends whose first source words are kept full and followed by clipped second source words. In morphopohonological process, there is no non-overlapping blends; phonological overlap also takes place, but not orthographical one. Morphosemantically, attributive blends are more frequent than the coordinative ones.